2022
DOI: 10.36469/001c.39768
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of the CNIC-Polypill Strategy Compared With Separate Monocomponents in Secondary Prevention of Cardiovascular and Cerebrovascular Disease in Portugal: The MERCURY Study

Abstract: Background: Cardiovascular (CV) diseases remain a leading and costly cause of death globally. Patients with previous CV events are at high risk of recurrence. Secondary prevention therapies improve CV risk factor control and reduce disease costs. Objectives: To assess the cost-effectiveness of a CV polypill strategy (CNIC-Polypill) compared with the loose combination of monocomponents to improve the control of CV risk factors in patients with previous coronary heart disease or stroke. Methods: A Markov model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…This result is in line with the results of the MERCURY cost-effectiveness analysis, where the CNIC-polypill strategy was cost-effective compared with monocomponents from the perspective of the National Health System in Portugal in patients who have suffered a CHD event or a stroke. 23 This is also in line with the conclusions of a recent systematic literature review where the CV polypill (consisting of ASA, a lipid-lowering agent, and at least one antihypertensive drug) was cost-effective compared with the standard treatment for secondary prevention in patients with at least one non-fatal coronary heart event. 59 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This result is in line with the results of the MERCURY cost-effectiveness analysis, where the CNIC-polypill strategy was cost-effective compared with monocomponents from the perspective of the National Health System in Portugal in patients who have suffered a CHD event or a stroke. 23 This is also in line with the conclusions of a recent systematic literature review where the CV polypill (consisting of ASA, a lipid-lowering agent, and at least one antihypertensive drug) was cost-effective compared with the standard treatment for secondary prevention in patients with at least one non-fatal coronary heart event. 59 …”
Section: Discussionsupporting
confidence: 83%
“… 22 Additionally, health economic assessments conducted in the MERCURY cost-effectiveness analysis (CEA) and model-based CEAs based on NEPTUNO effectiveness data concluded that the CNIC-polypill is a cost-effective therapeutic strategy compared with other approaches. 23–25 These findings underscore the growing body of evidence advocating for the incorporation of polypills in CV care. 26–28 …”
Section: Introductionmentioning
confidence: 83%
“…The incremental cost–utility ratio was €2328 per QALY in patients with coronary heart disease and €553/QALY in those with a previous stroke, being cost-effective for a threshold of €30,000/QALY. 37 …”
Section: Discussionmentioning
confidence: 99%
“…However, a recent meta-analysis of socioeconomic studies concluded that polypills resulted in improved adherence and quality of life at a price equal to or lower than multiple monotherapies, with the price (which was below the commonly accepted thresholds or cost saving in both primary and secondary prevention) as one of the key drivers of the cost-effectiveness [ 16 ]. Similarly, a cost-utility analysis conducted in Portugal documented that the CV polypill was consistently cost-effective compared with monocomponents in secondary prevention [ 17 ].…”
Section: Discussionmentioning
confidence: 99%